A silicone polymer, and a preparation method and application thereof

CN119661852BActive Publication Date: 2026-10-20QIANWAN INST OF CNITECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311204971.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2026-10-20
Estimated Expiration
2043-09-19

AI Technical Summary

Technical Problem

通过交联能减少低分子量的有机硅高分子的挥发,但是不饱和基团的引入,也会带来一些负面影响,比如残余碳含量的增加,而且过高的不饱和基团含量也会导致陶瓷产率降低

Benefits of technology

[0054](1)有利于获得高分子量的有机硅高分子;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661852B_ABST
    Figure CN119661852B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of SiC ceramics, and relates to an organic silicon polymer of SiC ceramic raw materials, a preparation method of the organic silicon polymer and application of the organic silicon polymer in conversion into SiC ceramics. The organic silicon polymer has a main chain formed by alternately connecting Si atoms and C atoms, and the main chain comprises a branched structure and / or a cyclic structure; the composition structure of the main chain comprises and / or a Si atom is independently connected with one or more selected from H, an alkyl group, an aryl group, a substituted aryl group and an unsaturated group to form sp 3 The introduction of the structure and / or can improve the molecular weight of the organic silicon polymer, reduce the content of the unsaturated group, and also has the effects of improving the reaction yield, reducing the residual C content, improving the ceramic yield and reducing the proportion of the -SiH3 group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of SiC ceramic technology, and relates to organosilicon polymers as raw materials for SiC ceramics, their preparation methods, and their applications in converting them into SiC ceramics. Background Technology

[0002] Organosilicon polymers with -Si-C- as the main chain and H, alkyl, aryl, or unsaturated groups attached to the Si and C atoms can be transformed into SiC ceramics of various forms through high-temperature pyrolysis. SiC ceramics possess excellent properties such as high hardness, high thermal conductivity, low creep, corrosion resistance, radiation resistance, high-temperature resistance, and oxidation resistance, making them ideal high-safety structural materials for extreme environments such as high temperature, strong neutron radiation, high-speed friction, and strong corrosion. Therefore, these organosilicon polymers have significant application value.

[0003] Grignard coupling is an important method for preparing this type of organosilicon polymer. It mainly uses Cl3SiCH2Cl (also written as ClCH2SiCl3) as a raw material. Magnesium effectively recognizes the Si-Cl and C-Cl bonds in its structure, selectively reacting only with C-Cl to form a Grignard reagent. The Grignard reagent couples with Si-Cl to form a chlorinated organosilicon polymer intermediate, which is then reduced to obtain the organosilicon polymer (Ackley BJ, Martin KL, Key TS, et al. Advances in the synthesis of preceramic polymers for the formation of silicon-based and ultrahigh-temperature non-oxide ceramics. Chem. Rev. 2023, 123, 4188-4236). Its structure is relatively complex, including branched and cyclic structures.

[0004] However, because the Si-Cl groups in the Cl3SiCH2Cl monomer readily undergo substitution reactions with ether solvents, these solvents are introduced into the organosilicon polymer through chemical bonds, leading to problems such as high oxygen content in the ceramic products. The current solution is to partially alkylate or alkoxylate the Si-Cl groups in Cl3SiCH2Cl.

[0005] Ideal organosilicon polymers require not only low oxygen content but also high ceramic yield. To this end, some unsaturated groups that can induce crosslinking have been introduced (including allyl, vinyl, ethynyl, and acrylate groups). Crosslinking can reduce the volatilization of low molecular weight organosilicon polymers; however, the introduction of unsaturated groups can also bring some negative effects, such as increased residual carbon content, and excessively high unsaturated group content can lead to a decrease in ceramic yield. For example, the literature (He LJ, Zhang ZB, Yang XG, Jiao LL, Li YM, Xu CH. Liquid polycarbosilanes: synthesis and evaluation as precursors for SiC ceramic. Polym. Int., 2015, 64(8): 979-985.) uses chloromethyltrimethoxysilane and vinyl magnesium chloride as raw materials to synthesize organosilicon polymers. When the molar ratio of chloromethyltrimethoxysilane to vinyl magnesium chloride increases from 6 / 1 to 1 / 6, the ceramic yield at 1000℃ gradually decreases from 63.8 wt% to 33.6 wt%; the C / Si ratio of the ceramic product increases from 1.48 to 3.46. Therefore, how to obtain an organosilicon polymer with high ceramic yield and low residual carbon content is a technical challenge in this field. Summary of the Invention

[0006] The purpose of this invention is to address the shortcomings of existing technologies by providing an organosilicon polymer with advantages such as high molecular weight, high ceramic yield, and low residual carbon content. This invention also provides a method for preparing the organosilicon polymer, through which a high yield of the polymer is obtained. Furthermore, this invention also provides applications of the organosilicon polymer.

[0007] The first objective of this invention is achieved through the following technical solution:

[0008] An organosilicon polymer having a main chain formed by alternating Si and C atoms, the main chain including a branched structure; the composition of the main chain includes... as well as and / or One or more groups selected from H, alkyl, aryl, substituted aryl, and unsaturated groups are independently attached to the Si atom to form sp. 3 Hybridization.

[0009] Optionally, the main chain of the organosilicon polymer of the present invention may also include a cyclic structure.

[0010] The main chain's structure includes as well as and / or Right now and / or Random or ordered connections form the main chain.

[0011] The principle behind this invention for designing organosilicon polymers is: in conventional... Introduced in the main chain structure and / or The interconnected structure increases the molecular weight of the organosilicon polymer, which helps ensure cross-linking and curing even with a slight reduction in the content of unsaturated groups. Therefore, the organosilicon polymer of this invention has the advantages of high molecular weight, no / low unsaturated group content, and also achieves the effects of improved reaction yield, increased ceramic yield, reduced residual carbon content, and improved stability.

[0012] structure and Can be used simultaneously with structure These structures exist within the main chain of the organosilicon polymer. At this point, the molar percentage of each structure among the three structures is between 1% and 90%, but the sum of the molar percentages of the three structures is 100%. and It can also be related to the structure separately. It exists within the main chain of the organosilicon polymer. However, its structure... The introduction of [a specific ingredient] has a more significant effect on increasing molecular weight and reaction yield.

[0013] Therefore, preferably, the organosilicon polymer provided by the present invention has a main chain formed by alternating Si atoms and C atoms, wherein the main chain includes a branched structure and / or a cyclic structure; the composition of the main chain includes and Not included One or more groups selected from H, alkyl, aryl, substituted aryl, and unsaturated groups are independently attached to the Si atom to form sp. 3 Hybridization.

[0014] In the above structure, in addition to bonding with C atoms, the Si atoms also independently attach one or more groups selected from H, alkyl, aryl, substituted aryl, and unsaturated groups to form sp. 3 Hybridization.

[0015] Optionally, the alkyl group attached to the Si atom is C1 to C2. 18 The alkyl group can be one or more of straight-chain alkyl, branched alkyl, and cyclic alkyl groups. Further, optionally, the alkyl group attached to the Si atom is C1 to C2. 12 Alkyl; optionally, the alkyl group attached to the Si atom is a C1 to C6 alkyl group.

[0016] Optionally, the aryl groups attached to the Si atoms are C6 to C6. 24Aryl group. Further, the aryl group is C6-C6. 18 Aryl group. Furthermore, the aryl group is C6-C6. 12 Aryl.

[0017] Any hydrogen atom on the aromatic ring of a Si atom with a substituted aryl group is independently affected by any C1 to C2 atoms. 18 Alkyl substitution.

[0018] Optionally, the unsaturated groups attached to the Si atoms are unsaturated groups containing C=C and / or C≡C.

[0019] Unsaturated groups containing C=C and / or C≡C can be listed as alkenyl, alkynyl, acrylate, alkenyl ether, alkynyl ether, etc.

[0020] However, the introduction of alkyl and unsaturated groups on the Si atoms will lead to an increase in the C / Si ratio in the organosilicon polymer, which is not conducive to improving the ceramic yield and the performance of the converted SiC ceramic and SiC ceramic matrix composite.

[0021] Preferably, the Si atoms are individually bonded to one or more groups selected from H and unsaturated groups to form sp 3 Hybridization. Furthermore, the content of unsaturated groups attached to Si atoms needs to be controlled. Therefore, as a further preferred embodiment, the molar ratio of Si atoms with unsaturated groups to the total Si atoms is 0.01 to 0.2. Even more preferred is that the molar ratio of Si atoms with unsaturated groups to the total Si atoms is 0.01 to 0.1.

[0022] Structure in the main chain and The content needs to be controlled; excessively high levels... and An excessively high content of certain substances can lead to excessively high molecular weights in the resulting organosilicon polymers, potentially causing them to cross-link into insoluble and non-meltable solids, losing their fluidity and thus reducing the reaction yield of the organosilicon polymers. Preferably, when the organosilicon polymer contains... and When there are two structures, the structure The molar amount of the two structures accounts for 1% to 60% of the total molar amount of the two structures. Further optimization is needed for the structure... The molar amount accounts for 10% to 50% of the total molar amount of these two structures; when the organosilicon polymer contains and When there are three structures, the structure and The molar amount of the three structures accounts for 1% to 60% of the total molar amount of the three structures. Further optimization is needed for the structure... and The molar amount accounts for 10% to 50% of the total molar amount of the three structures; when the organosilicon polymer contains and When there are two structures, the structure The molar amount of the two structures accounts for 1% to 50% of the total molar amount of the two structures. Further optimization is needed for the structure... The molar amount accounts for 10% to 40% of the total molar amount of the two structures.

[0023] The second objective of this invention is achieved through the following technical solution:

[0024] A method for preparing an organosilicon polymer includes the following steps:

[0025] by and / or as well as The monomer is used to prepare an organosilicon polymer through Grignard reaction and reduction reaction steps, wherein X is selected from one or more halogen groups; R1, R2, R3, R4, R5, R6, R7, R8 and R9 are independently selected from one or more of H, halogen, alkyl, alkoxy, aryl, substituted aryl and unsaturated groups; at least one of R1, R2 and R3 is a halogen or alkoxy group.

[0026] For the alkyl, aryl, substituted aryl, and unsaturated groups mentioned above, please refer to the relevant description in the organosilicon polymers provided in the first objective of this invention. Optionally, the alkoxy group is C1 to C2. 18 The alkoxy group can be straight-chain or branched; further, the alkoxy group is C1 to C2. 12 Alkoxy group; further, the alkoxy group is a C1-C6 alkoxy group; preferably, the alkoxy group is a methoxy group. The halogen group is F, Cl, Br or I.

[0027] To reduce residual carbon content, the structures R1, R2, R3, R4, R5, R6, R7, and R8 do not contain alkyl, aryl, or substituted aryl groups. Preferably, R1, R2, R3, R4, R5, R6, R7, R8, and R9 are independently selected from one or more of H, halogen, alkoxy, and unsaturated groups; at least one of R1, R2, and R3 is a halogen or alkoxy group.

[0028] In the preparation method of the present invention, if... As a monomer, it is prepared by Grignard reaction and reduction reaction steps to obtain a product containing the structure and Organosilicon polymers; if with As a monomer, it is prepared by Grignard reaction and reduction reaction steps to obtain a product containing the structure and Organosilicon polymers; if with As a monomer, it is prepared by Grignard reaction and reduction reaction steps to obtain a product containing the structure and Organosilicon polymers.

[0029] In the above preparation method, preferably, the Grignard reaction step includes: monomer and / or and monomers Magnesium metal undergoes a Grignard reaction in ether solvents to yield an intermediate of organosilicon polymer.

[0030] Preferably, the Grignard reaction step specifically includes: monomer as well as and / or Add to ether solvents containing magnesium, or add magnesium to solvents containing monomers. as well as and / or In an ether solvent, a Grignard reaction is carried out to obtain an intermediate of organosilicon polymer.

[0031] Studies have found that monomers that play a cross-linking role and / or In monomer Adding it after the reaction is more beneficial for increasing the molecular weight of the organosilicon polymer. Therefore, further optimization is needed, in the Grignard reaction step, the monomer... and / or The feeding time is later than The Grignard reaction step specifically includes: monomer... Add to an ether solvent containing magnesium metal, and after the feeding is complete, add... and / or A Grignard reaction is carried out to obtain an intermediate of organosilicon polymer.

[0032] As a preferred method, the temperature is controlled at 40–70°C during the feeding process.

[0033] Preferably, the Grignard reaction is carried out at 45–85°C for 1–50 h; more preferably, the Grignard reaction is carried out at 50–80°C for 5–40 h; even more preferably, the Grignard reaction is carried out at 60–80°C for 8–30 h.

[0034] This invention has found that, compared to monomers monomer Because it contains more CX groups, it is more beneficial to increase the molecular weight of the organosilicon polymer, and it can also reduce the use of expensive reducing agents. Therefore, preferably, the preparation method of the organosilicon polymer includes the following steps: using As a monomer, an organosilicon polymer is prepared through a Grignard reaction and a reduction reaction, wherein X is selected from one or more halogen groups; R1, R2, R3, R7, R8, and R9 are independently selected from one or more of H, halogen, alkyl, alkoxy, aryl, substituted aryl, and unsaturated groups; at least one of R1, R2, and R3 is a halogen or alkoxy group. The Grignard reaction step in this case includes: monomer... monomer Magnesium metal undergoes a Grignard reaction in ether solvents to yield an intermediate of organosilicon polymer.

[0035] Crosslinking groups are beneficial for the curing and molding of organosilicon polymers and for improving ceramic yield, in addition to using materials containing unsaturated groups. Alternatively, crosslinkable unsaturated groups can be introduced into organosilicon polymers by adding unsaturated haloalkanes and / or their Grignard reagents during the Grignard reaction step. In this case, the Grignard reaction step includes: monomer... and / or and monomers Metallic magnesium, unsaturated haloalkanes, and / or their Grignard reagents undergo a Grignard reaction in an ether solvent to yield an intermediate of an organosilicon polymer. Preferably, the unsaturated haloalkanes include CX groups, C=C groups, and / or C≡C groups, where X is a halogen element. More preferably, the unsaturated haloalkanes are olefins or alkynes containing CX groups. Examples of the unsaturated haloalkanes include one or more of vinyl bromide, vinyl chloride, allyl chloride, allyl bromide, propargyl chloride, propargyl bromide, ethynyl bromide, and ethynyl chloride. Examples of the Grignard reagents for the unsaturated haloalkanes include one or more of allyl magnesium chloride, vinyl magnesium bromide, vinyl magnesium chloride, propargyl magnesium chloride, ethynyl magnesium bromide, propargyl magnesium bromide, ethynyl magnesium chloride, and allyl magnesium bromide.

[0036] The number of unsaturated groups in organosilicon polymers needs to be controlled and cannot be too high. Therefore, preferably, the molar amount of unsaturated haloalkanes and / or their Grignard reagents is 0.005 to 0.2 of the total molar amount of the monomers; further, the molar amount of unsaturated haloalkanes and / or their Grignard reagents is 0.005 to 0.1 of the total molar amount of the monomers.

[0037] In the above-mentioned method for preparing organosilicon polymers, when it contains When three monomers are used, each monomer accounts for between 1% and 90% of the total molar percentage of the three monomers, but the sum of the molar percentages of the three monomers is 100%. Preferably, when containing... When there are two monomers, the monomers The molar amount of the monomer accounts for 1% to 60% of the total molar amount of the two monomers. Further preferred monomers... The molar amount of the component accounts for 10% to 50% of the total molar amount of the two monomers; when it contains When there are three monomers, the monomers The molar amount of the monomer accounts for 1% to 60% of the total molar amount of the three monomers. Further optimization is needed for the monomers... The molar amount of this component accounts for 10% to 50% of the total molar amount of the three monomers; when it contains When there are two monomers, the monomers The molar amount of the monomer accounts for 1% to 50% of the total molar amount of the two monomers. Further optimization is preferred, with the monomer... The molar amount of the two monomers accounts for 10% to 40% of the total molar amount of the two monomers.

[0038] Magnesium metal is used to form Grignard reagents with CX groups. Preferably, the molar amount of magnesium metal is greater than or equal to the sum of the molar amounts of all CX groups. More preferably, the molar amount of magnesium metal is 1.01 to 1.8 times the sum of the molar amounts of all CX groups. The CX groups mentioned herein include not only monomers... The CX group in it also includes the CX group in unsaturated haloalkanes.

[0039] Optionally, the ether solvent is selected from one or a mixture of two or more of tetrahydrofuran, 2-methyltetrahydrofuran, ethylene glycol dimethyl ether, ethylene glycol dibutyl ether, diethylene glycol dimethyl ether, methyl tert-butyl ether, methyl tert-amyl ether, cyclopentyl methyl ether, etc.

[0040] In the above-mentioned method for preparing organosilicon polymers, preferably, the reduction reaction step includes: adding a reducing agent to the product of the Grignard reaction to carry out a reduction reaction.

[0041] The reducing agent can be any effective reducing agent capable of reducing halogen groups and / or alkoxy groups on organosilicon polymer intermediates to H, including but not limited to one or more of LiAlH4, NaAlH4, red aluminum, NaBH4, NaH, and LiH. The reducing agent can be added in the form of solid powder or granules, or in the form of a solution dissolved or dispersed in a solvent.

[0042] Preferably, the reduction reaction is carried out at 45–85°C for 1–40 h; more preferably, the reduction reaction is carried out at 50–80°C for 2–30 h; even more preferably, the reduction reaction is carried out at 60–80°C for 2–20 h.

[0043] The principle for the amount of reducing agent added is that the molar amount of effective reduced hydrogen in the reducing agent is greater than or equal to the molar amount of halogen groups and alkoxy groups in the intermediate structure of the organosilicon polymer.

[0044] In the above-mentioned method for preparing organosilicon polymers, preferably, after the Grignard reaction step and the reduction reaction step, an extraction and concentration step is also performed. The extraction and concentration step includes: mixing the reduction reaction product with an acidic aqueous solution and extracting it with an organic extractant; concentrating the organic phase obtained from the extraction to remove the organic extractant, thereby obtaining the organosilicon polymer.

[0045] The reduction reaction product is mixed with an acidic aqueous solution, preferably at a temperature below 0 degrees Celsius. The acidic aqueous solution can be hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, etc., with a concentration ranging from 1 to 10 mol / L. The mixture of the reduction reaction product and the acidic aqueous solution is extracted with an organic extractant to obtain an organic phase containing the organosilicon polymer and an aqueous solution containing inorganic magnesium, lithium, sodium, or aluminum salts. The organic phase and the aqueous solution are separated by liquid-liquid extraction. The organic extractant can be selected from low-boiling-point solvents that are sparingly soluble in water but can dissolve the organosilicon polymer, such as petroleum ether, diethyl ether, halogenated hydrocarbons, hexane, heptane, octane, benzene, and toluene.

[0046] The third objective of this invention is achieved through the following technical solution:

[0047] An application of an organosilicon polymer, said application including one or more of the following:

[0048] a. Applied to the preparation of SiC ceramic matrix composites, porous SiC ceramics, or SiC fibers.

[0049] b. Preparation of protective coatings for use on carbon materials, metals, ceramics, or ceramic matrix composites.

[0050] c. Applied for filling and / or reinforcing carbon materials, metals, ceramics, or ceramic matrix composites.

[0051] d. Applied to the joining of ceramics or ceramic matrix composites,

[0052] e. Applied to the molding of complex SiC ceramic components.

[0053] Compared with the prior art, the present invention uses conventional methods... Introduced into organosilicon polymers with main chain structure and / or The structure has the following beneficial effects:

[0054] (1) It is beneficial to obtain high molecular weight organosilicon polymers;

[0055] (2) The increased molecular weight of organosilicon polymers helps to reduce the content of carbon-rich unsaturated groups, thereby reducing the residual carbon in the converted SiC ceramics.

[0056] (3) It helps to improve the storage stability of organosilicon polymers;

[0057] (4) Compared to monomers monomer The introduction of [the substance] has a more significant effect on increasing the molecular weight of organosilicon polymers, reducing the content of cross-linking groups, and the C / Si ratio;

[0058] (5) The method for preparing organosilicon polymers of the present invention has a higher reaction yield;

[0059] (6) The organosilicon polymer of the present invention has a higher ceramic yield;

[0060] (7) The structural modification of the organosilicon polymer does not affect the application of the organosilicon polymer in high-temperature pyrolysis to silicon carbide ceramics. Attached Figure Description

[0061] Figure 1 The 1H NMR spectrum of the organosilicon polymer described in Comparative Example 1 of this invention;

[0062] Figure 2 The 1H NMR spectrum of the organosilicon polymer described in Example 1 of this invention;

[0063] Figure 3 The XRD pattern of the organosilicon polymer described in Example 4 of this invention;

[0064] Figure 4 SEM image of carbon fibers with a SiC protective coating on the surface prepared in Example 18 of the present invention. Detailed Implementation

[0065] The technical solution of the present invention will be further described and illustrated below with reference to specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the specific scope of the present invention. Furthermore, the accompanying drawings used herein are merely for better illustrating the content disclosed in the present invention and do not have a limiting effect on the scope of protection.

[0066] The performance tests in the following comparative examples and embodiments were performed using the following instruments:

[0067] MRI: Tested using a Bruker Avance III MRI scanner from Bruker GmbH, Germany;

[0068] Molecular weight: determined using a TOSOH HLC-8320GPC gel permeation chromatograph (Japan).

[0069] Oxygen content: tested using a HORIBA EMGA-620 oxygen and nitrogen analyzer (Japan).

[0070] Thermogravimetric analysis: Tested using a TG-DTA 6300 thermogravimetric analyzer manufactured by Seiko AG, Japan;

[0071] X-ray diffraction: Tested using a Bruker D8 Advance polycrystalline X-ray diffractometer from Germany.

[0072] Three-point bending strength: tested using a German Zwick 30KN material testing machine.

[0073] Comparative Example 1

[0074] 368 g of ClCH₂SiCl₃ was added in one go to a 1000 mL two-necked flask equipped with a dropping funnel and a gas delivery tube, followed by 112 g of CH₃OH. The reaction was then continued at room temperature for 2 hours. The HCl produced in the reaction was neutralized by absorption with NaOH aqueous solution to obtain ClCH₂SiCl₃. 1.25 (CH3O) 1.75 (It is a mixture of ClCH2SiCl2(CH3O), ClCH2SiCl(CH3O)2 and ClCH2Si(CH3O)3. According to NMR calculations, the molar ratio of the three is approximately 0.36:0.53:0.11).

[0075] Under nitrogen protection, magnesium (18.7 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl was slowly added dropwise through the dropping funnel. 1.25 (CH3O) 1.75 (88g) and allyl chloride (3.8g). After the addition of the materials, the reaction was maintained at 65℃ for 12h. Then, the temperature was lowered to room temperature, LiAlH4 (11.7g) was added, and the reaction was maintained at 65℃ for 12h.

[0076] The reaction solution was mixed with an aqueous HCl solution (330 mL, 4 mol / L) at 0 °C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. The upper organic phase was separated, dried over Na₂SO₄, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa) to obtain 16.3 g of liquid organosilicon polymer, with a reaction yield of 67.9%. Gel permeation chromatography analysis showed a number-average molecular weight of 783 and a weight-average molecular weight of 1703. The NMR spectrum is attached. Figure 1 As shown, the -SiH3 structure exists in all -SiH x The proportion of the sample is 30%. Take 0.5 mL and spread it evenly on a glass slide with a size of 25*75 mm. Place it in a constant temperature incubator at 35℃ and it will gel after 25 h.

[0077] The obtained liquid organosilicon polymer (2g) was mixed evenly with tert-butyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Afterwards, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 75.2%. Elemental analysis showed that the C content was 33.09wt%, the O content was 1.53wt%, and the Si content was 65.38wt% (obtained by subtraction), resulting in a C / Si ratio of 1.18.

[0078] Comparative Example 2

[0079] 368 g of ClCH₂SiCl₃ was added in one go to a 1000 mL two-necked flask equipped with a dropping funnel and a gas delivery tube, followed by 144 g of CH₃OH. The reaction was then continued at room temperature for 2 hours. The HCl produced in the reaction was neutralized by absorption with NaOH aqueous solution to obtain ClCH₂SiCl₃. 0.75 (CH3O) 2.25 (It is a mixture of ClCH2SiCl2(CH3O), ClCH2SiCl(CH3O)2 and ClCH2Si(CH3O)3. According to NMR calculations, the molar ratio of the three is approximately 0.13:0.49:0.38).

[0080] Under nitrogen protection, magnesium (18.7 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl was slowly added dropwise through the dropping funnel. 0.75 (CH3O) 2.25 (87g) and ethylene bromide (5.4g). After the addition was completed, the reaction was maintained at 65℃ for 15h. Then, the temperature was lowered to room temperature, and LiAlH4 (11.7g) was added and the reaction was maintained at 65℃ for 12h.

[0081] The reaction solution was mixed with an aqueous HCl solution (330 mL, 4 mol / L) at 0 °C, and the synthesized organosilicon polymer was extracted with diethyl ether (360 mL). The upper organic phase was separated, dried over Na₂SO₄, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa) to obtain 15.4 g of liquid organosilicon polymer, with a reaction yield of 66.1%. Gel permeation chromatography analysis showed a number-average molecular weight of 842 and a weight-average molecular weight of 1824.

[0082] Liquid organosilicon polymer (2g) was mixed evenly with benzoyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Afterwards, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 78.2%. Elemental analysis showed that the C content was 32.49wt%, the O content was 1.37wt%, and the Si content was 66.14wt% (obtained by subtraction), resulting in a C / Si ratio of 1.15.

[0083] Comparative Example 3

[0084] Under nitrogen protection, magnesium (18.4 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl synthesized in Comparative Example 1 was slowly added dropwise through the dropping funnel. 1.25 (CH3O) 1.75 (88g) and allyl chloride (3.1g). After the addition of the materials, the reaction was maintained at 65℃ for 12h. Then, the temperature was lowered to room temperature, LiAlH4 (11.9g) was added, and the reaction was maintained at 65℃ for 12h.

[0085] The reaction solution was mixed with an aqueous HCl solution (325 mL, 4 mol / L) at 0 °C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. The upper organic phase was separated, dried over Na2SO4, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa) to obtain 15.7 g of liquid organosilicon polymer, with a reaction yield of 66.5%. Gel permeation chromatography analysis showed a number average molecular weight of 764 and a weight average molecular weight of 1732.

[0086] Liquid organosilicon polymer (2g) was mixed evenly with tert-butyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Afterwards, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 73.2%. Elemental analysis showed that the C content was 32.38wt%, the O content was 1.81wt%, and the Si content was 65.81wt% (obtained by subtraction), resulting in a C / Si ratio of 1.15.

[0087] Comparative Example 4

[0088] Under nitrogen protection, magnesium (17 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl synthesized in Comparative Example 1 was slowly added dropwise through the dropping funnel. 1.25 (CH3O) 1.75(88g). After the feeding was completed, the reaction was kept at 65℃ for 12h. Then, the temperature was lowered to room temperature, LiAlH4 (12.4g) was added, and the reaction was kept at 65℃ for 12h.

[0089] The reaction solution was mixed with an aqueous HCl solution (310 mL, 4 mol / L) at 0 °C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. The upper organic phase was separated, dried over Na2SO4, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa) to obtain 14.1 g of liquid organosilicon polymer, with a reaction yield of 64%. Gel permeation chromatography analysis showed a number average molecular weight of 730 and a weight average molecular weight of 1639.

[0090] Due to the absence of unsaturated groups, the mass retention rate was only 43.6% when heated to 1000℃ in a thermogravimetric analyzer at a rate of 10℃ / min. Elemental analysis showed that the C content was 29.75wt%, the O content was 1.53wt%, and the Si content was 68.72wt% obtained by subtraction, with a C / Si ratio of 1.01.

[0091] Example 1

[0092] 506 g of Cl3CSiCl3 was added in one go to a 1000 mL two-necked flask equipped with a dropping funnel and a gas delivery tube, followed by 112 g of CH3OH. The mixture was then reacted at room temperature for 2 hours. The HCl produced in the reaction was neutralized by absorption with NaOH aqueous solution to obtain Cl3CSiCl3. 1.25 (CH3O) 1.75 (It is a mixture of Cl3CSiCl2(CH3O), Cl3CSiCl(CH3O)2 and Cl3CSi(CH3O)3. According to NMR calculations, the molar ratio of the three is approximately 0.34:0.57:0.09).

[0093] Under nitrogen protection, magnesium (25.5 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl synthesized in Comparative Example 1 was added sequentially through the dropping funnel. 1.25 (CH3O) 1.75 (70.5g) and the Cl3CSiCl synthesized in this example 1.25 (CH3O) 1.75 A mixture of (24.5g) and allyl chloride (3.8g) was formed. After the addition of the raw materials, the reaction was maintained at 65℃ for 12h. The temperature of the reaction solution was then lowered to room temperature, and then LiAlH4 (9.3g) was added, and the reaction was maintained at 65℃ for 12h.

[0094] The reaction solution was mixed with an aqueous HCl solution (450 mL, 4 mol / L) at 0 °C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. The upper organic phase was separated, dried over Na₂SO₄, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa). 20.3 g of liquid organosilicon polymer was obtained, with a reaction yield of 85.9%. Gel permeation chromatography analysis showed a number-average molecular weight of 1836 and a weight-average molecular weight of 7290. The NMR spectrum is attached. Figure 2 As shown, the -SiH3 structure exists in all -SiH x The proportion of the sample was 22%. 0.5 mL was evenly spread onto a 25*75 mm glass slide and placed in a 35℃ incubator. After 68 hours, the sample gelled.

[0095] Liquid organosilicon polymer (2g) was mixed evenly with tert-butyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Afterwards, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 83.9%. Elemental analysis showed that the C content was 32.51wt%, the O content was 1.71wt%, and the Si content was 65.78wt% (obtained by subtraction), resulting in a C / Si ratio of 1.15.

[0096] Example 2

[0097] 506 g of Cl3CSiCl3 was added in one go to a 1000 mL two-necked flask equipped with a dropping funnel and a gas delivery tube, followed by 144 g of CH3OH. The mixture was then reacted at room temperature for 2 hours. The HCl produced in the reaction was neutralized by absorption with NaOH aqueous solution to obtain Cl3CSiCl3. 0.75 (CH3O) 2.25 (It is a mixture of Cl3CSiCl2(CH3O), Cl3CSiCl(CH3O)2 and Cl3CSi(CH3O)3. According to NMR calculations, the molar ratio of the three is approximately 0.11:0.53:0.36).

[0098] Under nitrogen protection, magnesium (22.1 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl synthesized in Comparative Example 2 was added sequentially through the dropping funnel. 0.75 (CH3O) 2.25 (78.3g) and the Cl3CSiCl synthesized in this example 0.75 (CH3O) 2.25A mixture of 12.1 g and 5.4 g of ethylene bromide was formed. After the addition was completed, the mixture was kept at 65 °C for 15 h. Then, the temperature was lowered to room temperature, and 10.5 g of LiAlH4 was added and the mixture was kept at 65 °C for 12 h.

[0099] The reaction solution was mixed with an aqueous HCl solution (390 mL, 4 mol / L) at 0 °C, and the synthesized organosilicon polymer was extracted with diethyl ether (360 mL). The upper organic phase was separated, dried over Na₂SO₄, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa) to obtain 17.3 g of liquid organosilicon polymer, with a reaction yield of 75.1%. Gel permeation chromatography analysis showed a number-average molecular weight of 1158 and a weight-average molecular weight of 3027.

[0100] Liquid organosilicon polymer (2g) was mixed evenly with benzoyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Afterwards, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 79.3%. Elemental analysis showed that the C content was 32.31wt%, the O content was 1.41wt%, and the Si content was 66.28wt% (obtained by subtraction), resulting in a C / Si ratio of 1.14.

[0101] Example 3

[0102] Under nitrogen protection, magnesium (25.2 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl synthesized in Comparative Example 1 was added sequentially through the dropping funnel. 1.25 (CH3O) 1.75 (70.5g) and Cl3CSiCl synthesized in Example 1 1.25 (CH3O) 1.75 A mixture of (24.5g) and allyl chloride (3.1g) was formed. After the addition of the reactants, the reaction was maintained at 65℃ for 12h. The temperature of the reaction solution was then lowered to room temperature, and then LiAlH4 (9.4g) was added, and the reaction was maintained at 65℃ for 12h.

[0103] The reaction solution was mixed with an aqueous HCl solution (445 mL, 4 mol / L) at 0 °C, and the synthesized organosilicon polymer was extracted with n-hexane (360 mL). The upper organic phase was separated, dried over Na₂SO₄, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa). 20.0 g of liquid organosilicon polymer was obtained, with a reaction yield of 86.2%. Gel permeation chromatography analysis showed a number-average molecular weight of 1949 and a weight-average molecular weight of 7002.

[0104] Liquid organosilicon polymer (2g) was mixed evenly with tert-butyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Afterwards, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 84.3%. Elemental analysis showed that the C content was 31.78wt%, the O content was 1.72wt%, and the Si content was 66.5wt% (obtained by subtraction), resulting in a C / Si ratio of 1.12.

[0105] Example 4

[0106] Under nitrogen protection, magnesium (24.5 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl was added sequentially through the dropping funnel. 1.25 (CH3O) 1.75 (70.5g) and Cl3CSiCl 1.25 (CH3O) 1.75 A mixture of 24.5g and allyl chloride (1.52g) was formed. After the addition of the raw materials, the reaction was maintained at 65℃ for 12h. The temperature of the reaction solution was then lowered to room temperature, and then LiAlH4 (9.6g) was added, and the reaction was maintained at 65℃ for 12h.

[0107] The reaction solution was mixed with an aqueous HCl solution (430 mL, 4 mol / L) at 0 °C, and the synthesized organosilicon polymer was extracted with n-hexane (360 mL). The upper organic phase was separated, dried over Na₂SO₄, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa). 18.9 g of liquid organosilicon polymer was obtained, with a reaction yield of 84.2%. Gel permeation chromatography analysis showed a number-average molecular weight of 1894 and a weight-average molecular weight of 7078.

[0108] Liquid organosilicon polymer (2g) was mixed evenly with tert-butyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Afterwards, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 83.9%. Elemental analysis showed a C content of 30.52wt%, an O content of 1.70wt%, and a Si content of 67.78wt% (obtained by subtraction), resulting in a C / Si ratio of 1.05. Further pyrolysis to 1600℃ yielded a mass retention rate of 83.1%. X-ray diffraction is shown in the attached figure. Figure 3 As shown, it exhibits typical SiC crystallization diffraction peaks.

[0109] Example 5

[0110] Under nitrogen protection, magnesium (35.7 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl was added sequentially through the dropping funnel. 0.75 (CH3O) 2.25 (43.5g) and Cl3CSiCl 0.75 (CH3O) 2.25 A mixture of (60.7g) and ethylene bromide (5.4g) was formed. After the addition of the feed, the reaction was maintained at 65℃ for 12h. The temperature of the reaction solution was then lowered to room temperature, and then LiAlH4 (5.6g) was added, and the reaction was maintained at 65℃ for 12h.

[0111] The reaction solution was mixed with an aqueous HCl solution (630 mL, 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. Compared to Example 2, the amount of suspended solids in the intermediate phase was significantly increased. The upper organic phase was separated, dried with Na2SO4, and distilled under reduced pressure (maximum distillation temperature 60°C, pressure gauge readings -0.093 to -0.096 MPa). 14.5 g of liquid organosilicon polymer was obtained, with a reaction yield of only 65%. Analysis of the suspended solids in the water showed that their infrared structure was consistent with the obtained liquid organosilicon polymer, suggesting that it was a highly cross-linked organosilicon polymer. This cross-linking made it difficult to dissolve, thus affecting the reaction yield.

[0112] Example 6

[0113] Under nitrogen protection, magnesium (24.5 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl was added sequentially through the dropping funnel. 1.25 (CH3O) 1.75 (70.5g), Cl3CSiCl 1.25 (CH3O) 1.75 (24.5g) and allyl chloride (1.52g). After the addition of the materials, the reaction was maintained at 65℃ for 12h. The temperature of the reaction solution was then lowered to room temperature, and then LiAlH4 (9.6g) was added, and the reaction was maintained at 65℃ for 12h.

[0114] The reaction solution was mixed with an aqueous HCl solution (430 mL, 4 mol / L) at 0 °C, and the synthesized organosilicon polymer was extracted with n-hexane (360 mL). The upper organic phase was separated, dried over Na₂SO₄, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa). 19.3 g of liquid organosilicon polymer was obtained, with a reaction yield of 86.3%. Gel permeation chromatography analysis showed a number-average molecular weight of 1974 and a weight-average molecular weight of 7693.

[0115] Liquid organosilicon polymer (2g) was mixed evenly with tert-butyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Subsequently, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 84.4%. Elemental analysis showed that the C content was 30.54wt%, the O content was 1.63wt%, and the Si content was 67.83wt% (obtained by subtraction), resulting in a C / Si ratio of 1.05.

[0116] Example 7

[0117] Under nitrogen protection, magnesium (23.8 g) and tetrahydrofuran (310 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl synthesized in Comparative Example 1 was added sequentially through the dropping funnel. 1.25 (CH3O) 1.75 (70.5g) and Cl3CSiCl synthesized in Example 1 1.25 (CH3O) 1.75 A mixture of (24.5 g) and a tetrahydrofuran solution of acetylenyl magnesium bromide (50 mL, 1 mol / L) were formed. After the addition of the reactants, the reaction was maintained at 65 °C for 12 h. The reaction solution was then cooled to room temperature, and LiAlH4 (9.3 g) was added, and the reaction was maintained at 65 °C for 12 h.

[0118] The reaction solution was mixed with an aqueous HCl solution (420 mL, 4 mol / L) at 0 °C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. The upper organic phase was separated, dried over Na2SO4, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa). 19.2 g of liquid organosilicon polymer was obtained, with a reaction yield of 84.0%. Gel permeation chromatography analysis showed a number-average molecular weight of 1730 and a weight-average molecular weight of 6932.

[0119] Liquid organosilicon polymer (2g) was mixed evenly with tert-butyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Afterwards, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 84.1%. Elemental analysis showed that the C content was 32.14wt%, the O content was 1.46wt%, and the Si content was 66.40wt% (obtained by subtraction), resulting in a C / Si ratio of 1.13.

[0120] Example 8

[0121] 437 g of Cl₂CHSiCl₃ was added in one go to a 1000 mL two-necked flask equipped with a dropping funnel and a gas delivery tube, followed by 112 g of CH₃OH. The mixture was then reacted at room temperature for 2 hours. The HCl produced in the reaction was neutralized by absorption with NaOH aqueous solution to obtain Cl₂CHSiCl₃. 1.25 (CH3O) 1.75 (It is a mixture of Cl2CHSiCl2(CH3O), Cl2CHSiCl(CH3O)2 and Cl2CHSi(CH3O)3. According to NMR calculations, the molar ratio of the three is approximately 0.33:0.59:0.08).

[0122] Under nitrogen protection, magnesium (22.1 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl synthesized in Comparative Example 1 was added sequentially through the dropping funnel. 1.25 (CH3O) 1.75 (70.5g) and the Cl2CHSiCl synthesized in this example 1.25 (CH3O) 1.75 A mixture of 21.0 g and allyl chloride (3.8 g) was formed. After the addition was completed, the reaction was maintained at 65 °C for 12 h. The reaction solution temperature was then lowered to room temperature, and LiAlH4 (10.5 g) was added, and the reaction was maintained at 65 °C for 12 h.

[0123] The reaction solution was mixed with an aqueous HCl solution (390 mL, 4 mol / L) at 0 °C, and the synthesized organosilicon polymer was extracted with n-hexane (360 mL). The upper organic phase was separated, dried over Na₂SO₄, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa). 18.2 g of liquid organosilicon polymer was obtained, with a reaction yield of 76.3%. Gel permeation chromatography analysis showed a number-average molecular weight of 1352 and a weight-average molecular weight of 4268.

[0124] Liquid organosilicon polymer (2g) was mixed evenly with tert-butyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Afterwards, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 78.4%. Elemental analysis showed that the C content was 32.53wt%, the O content was 1.66wt%, and the Si content was 65.81wt% (obtained by subtraction), resulting in a C / Si ratio of 1.15.

[0125] Example 9

[0126] Under nitrogen protection, magnesium (23.8 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl synthesized in Comparative Example 1 was added sequentially through the dropping funnel. 1.25 (CH3O) 1.75 (70.5g), Cl3CSiCl synthesized in Example 1 1.25 (CH3O) 1.75 (12.3g) and Cl2CHSiCl synthesized in Example 8 1.25 (CH3O) 1.75 A mixture of 10.5g and allyl chloride (3.8g) was formed. After the addition of the raw materials, the reaction was maintained at 65°C for 12 hours. The temperature of the reaction solution was then lowered to room temperature, and then LiAlH4 (9.9g) was added, and the reaction was maintained at 65°C for 12 hours.

[0127] The reaction solution was mixed with an aqueous HCl solution (420 mL, 4 mol / L) at 0 °C, and the synthesized organosilicon polymer was extracted with n-hexane (360 mL). The upper organic phase was separated, dried over Na₂SO₄, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa). 18.7 g of liquid organosilicon polymer was obtained, with a reaction yield of 79.1%. Gel permeation chromatography analysis showed a number-average molecular weight of 1539 and a weight-average molecular weight of 5397.

[0128] Liquid organosilicon polymer (2g) was mixed evenly with tert-butyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Afterwards, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 80.4%. Elemental analysis showed that the C content was 32.55wt%, the O content was 1.61wt%, and the Si content was 65.84wt% (obtained by subtraction), resulting in a C / Si ratio of 1.15.

[0129] Example 10

[0130] Under nitrogen protection, magnesium (28.9 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl synthesized in Comparative Example 1 was added sequentially through the dropping funnel. 1.25 (CH3O) 1.75 (35.2g) and Cl2CHSiCl synthesized in Example 8 1.25 (CH3O) 1.75 A mixture of 63.2g and allyl chloride (3.8g) was formed. After the addition of the reactants, the reaction was maintained at 65°C for 12 hours. The temperature of the reaction solution was then lowered to room temperature, and LiAlH4 (8.0g) was added, and the reaction was maintained at 65°C for 12 hours.

[0131] The reaction solution was mixed with an aqueous HCl solution (510 mL, 4 mol / L) at 0°C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. Compared with Example 8, the amount of suspended solids in the intermediate phase was significantly increased. The upper organic phase was separated, dried with Na2SO4, and distilled under reduced pressure (maximum distillation temperature 60°C, pressure gauge readings -0.093 to -0.096 MPa). 15.7 g of liquid organosilicon polymer was obtained, with a reaction yield of only 67.1%, comparable to Comparative Example 1. Analysis of the suspended solids in water showed that their infrared structure was consistent with the obtained liquid organosilicon polymer, suggesting that it was a highly cross-linked organosilicon polymer. Due to cross-linking, it was difficult to dissolve, thus affecting the reaction yield.

[0132] Example 11

[0133] Under nitrogen protection, magnesium (32.3 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl was added sequentially through the dropping funnel. 0.75 (CH3O) 2.25 (52.2g) and Cl3CSiCl 0.75 (CH3O) 2.25 The mixture was formed from (48.6g) and ethylene bromide (5.4g). After the addition was completed, the reaction was maintained at 65℃ for 12h. The temperature of the reaction solution was lowered to room temperature, and then LiAlH4 (6.8g) was added, and the reaction was maintained at 65℃ for 12h.

[0134] The reaction solution was mixed with 570 mL of HCl aqueous solution (4 mol / L) at 0 °C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. The upper organic phase was separated, dried with Na2SO4, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa) to obtain 17.8 g of liquid organosilicon polymer, with a reaction yield of 79%. Gel permeation chromatography analysis showed a number average molecular weight of 2139 and a weight average molecular weight of 13852.

[0135] Liquid organosilicon polymer (2g) was mixed evenly with benzoyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Afterwards, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 88.1%. Elemental analysis showed that the C content was 32.25wt%, the O content was 1.54wt%, and the Si content was 66.21wt% (obtained by subtraction), resulting in a C / Si ratio of 1.14.

[0136] Example 12

[0137] Under nitrogen protection, magnesium (27.2 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl synthesized in Comparative Example 1 was added sequentially through the dropping funnel. 1.25 (CH3O) 1.75 (44.0 g) and Cl2CHSiCl synthesized in Example 8 1.25 (CH3O) 1.75 A mixture of 52.7g and allyl chloride (3.8g) was formed. After the addition of the raw materials, the reaction was maintained at 65℃ for 12h. The temperature of the reaction solution was then lowered to room temperature, and then LiAlH4 (8.7g) was added, and the reaction was maintained at 65℃ for 12h.

[0138] The reaction solution was mixed with an aqueous HCl solution (480 mL, 4 mol / L) at 0 °C, and the synthesized organosilicon polymer was extracted with n-hexane (360 mL). The upper organic phase was separated, dried over Na₂SO₄, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa). 18.5 g of liquid organosilicon polymer was obtained, with a reaction yield of 78.5%. Gel permeation chromatography analysis showed a number-average molecular weight of 1794 and a weight-average molecular weight of 8402.

[0139] Liquid organosilicon polymer (2g) was mixed evenly with tert-butyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Subsequently, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 82.9%. Elemental analysis showed that the C content was 32.60wt%, the O content was 1.40wt%, and the Si content was 66wt% (obtained by subtraction), resulting in a C / Si ratio of 1.15.

[0140] Example 13

[0141] Under nitrogen protection, magnesium (27.3 g) and tetrahydrofuran (400 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 60 °C. Then, ClCH₂SiCl synthesized in Comparative Example 1 was added sequentially through the dropping funnel. 1.25 (CH3O) 1.75 (70.5g) and Cl3CSiCl synthesized in Example 1 1.25 (CH3O) 1.75 A mixture of (24.5g) and allyl chloride (3.8g) was formed. After the addition of the raw materials, the reaction was maintained at 65℃ for 20h. The temperature of the reaction solution was then lowered to room temperature, and then NaAlH4 (15g) was added, and the reaction was maintained at 65℃ for 10h.

[0142] The reaction solution was mixed with 400 mL of HCl aqueous solution (5 mol / L) at -10 °C, and toluene (400 mL) was added to extract the synthesized organosilicon polymer. The upper organic phase was separated, dried over Na₂SO₄, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa). 18.9 g of liquid organosilicon polymer was obtained, with a reaction yield of 80%. Gel permeation chromatography analysis showed a number-average molecular weight of 1872 and a weight-average molecular weight of 7105.

[0143] Liquid organosilicon polymer (2g) was mixed evenly with tert-butyl peroxide (0.02g), and then cured at 120℃ for 1h under a nitrogen atmosphere. Afterwards, the temperature was increased to 1000℃ at a rate of 10℃ / min using a thermogravimetric analyzer, with a mass retention rate of 84.0%. Elemental analysis showed that the C content was 32.62wt%, the O content was 1.39wt%, and the Si content was 65.99wt% (obtained by subtraction), resulting in a C / Si ratio of 1.15.

[0144] Example 14

[0145] Under nitrogen protection, magnesium (27.2 g) and tetrahydrofuran (360 mL) were added to a four-necked flask equipped with a nitrogen inlet tube, condenser, and dropping funnel, and the temperature was raised to 55 °C. Then, ClCH₂SiCl synthesized in Comparative Example 1 was slowly added dropwise through the dropping funnel. 1.25 (CH3O) 1.75 (61.6g) and Cl3CSiCl synthesized in Example 1 1.25 (CH3O) 1.75 A mixture of (36.8g) was formed. After the addition was completed, the mixture was kept at 65℃ for 12h. Then, it was cooled to room temperature, and LiAlH4 (8.6g) was added and the mixture was kept at 65℃ for 12h.

[0146] The reaction solution was mixed with an aqueous HCl solution (480 mL, 4 mol / L) at 0 °C, and n-hexane (360 mL) was added to extract the synthesized organosilicon polymer. The upper organic phase was separated, dried over Na2SO4, and distilled under reduced pressure (maximum distillation temperature 60 °C, pressure gauge readings from -0.093 to -0.096 MPa) to obtain 17.8 g of liquid organosilicon polymer, with a reaction yield of 83%. Gel permeation chromatography analysis showed a number-average molecular weight of 1963 and a weight-average molecular weight of 10314.

[0147] Since there are no unsaturated groups, the mass retention rate was 70% when heated to 1000℃ in a thermogravimetric analyzer at a rate of 10℃ / min. Elemental analysis showed that the C content was 29.78wt%, the O content was 1.43wt%, and the Si content was 68.79wt% obtained by difference method, with a C / Si ratio of 1.01.

[0148] Example 15

[0149] The organosilicon polymer prepared in Example 2 is applied to SiC f Preparation of / SiC composite materials.

[0150] The SiC f The / SiC composite material was prepared by the following method:

[0151] Using CH4 as the carbon precursor and third-generation two-dimensional SiC fiber cloth as the reinforcement, a pyrolytic carbon layer was formed on the surface of SiC fibers at a deposition temperature of 1000℃, a deposition pressure of 5kPa, and a deposition time of 5h. 9.1g of silicon powder with an average particle size of 50nm, 0.09g of polyvinyl alcohol, 1.0g of tert-butyl peroxide, and 0.05g of tert-butylcatechol were added to 100mL of tetrahydrofuran and ball-milled at high speed for 10h. Then, 100g of liquid organosilicon polymer with a C / S ratio of 1.14 (prepared according to Example 2) was added, stirred evenly, and the tetrahydrofuran was extracted under reduced pressure. The SiC fiber cloth with the pyrolytic carbon layer deposited on the surface was then impregnated. The fully impregnated SiC fiber cloth was clamped in a graphite fixture and pyrolyzed at 2℃ / min to 1450℃ and held for 1h. This impregnation-pyrolysis cycle was repeated 10 times to obtain SiC fibers. f / SiC composite material. The room temperature three-point flexural strength is 530 MPa.

[0152] Example 16

[0153] The organosilicon polymer prepared in Example 2 is applied to SiC f Preparation of / SiC composite materials.

[0154] The SiC f The / SiC composite material was prepared by the following method:

[0155] 20g of SiC powder with an average particle size of 40nm, 0.5g of commercially available ZY-DP dispersant from Hunan Zhongyan Building Materials Technology Co., Ltd., and 1.0g of benzoyl peroxide were added to 100g of liquid organosilicon polymer with a C / S ratio of 1.14 prepared according to Example 2, and stirred until homogeneous. Then, the mixture was impregnated with SiC fiber cloth with a pyrolytic carbon layer deposited on the surface, prepared according to Example 14. The fully impregnated SiC fiber cloth was sandwiched in a graphite fixture and then pyrolyzed at 2℃ / min to 1200℃ and held at that temperature for 1h. This impregnation and pyrolysis cycle was repeated 10 times to obtain SiC... f / SiC composite material. The room temperature three-point flexural strength is 670 MPa.

[0156] Example 17

[0157] The organosilicon polymer prepared in Example 4 is applied to C f Preparation of / SiC composite materials.

[0158] The C f The / SiC composite material was prepared by the following method:

[0159] Using CH4 as the carbon precursor and C fiber cloth as the reinforcement, a pyrolytic carbon layer was formed on the surface of the C fibers at a deposition temperature of 1000℃, a deposition pressure of 5 kPa, and a deposition time of 4 h. The C fiber cloth was then sandwiched in a graphite fixture and impregnated with a liquid organosilicon polymer (C / Si ratio 1.05 synthesized in Example 4). The temperature was then increased to 1200℃ at a rate of 2℃ / min and held at 150℃, 180℃, and 1200℃ for 1 h each. This impregnation-pyrolysis cycle was repeated 10 times to obtain C... f / SiC composite material. The room temperature three-point flexural strength is 490 MPa.

[0160] Example 18

[0161] The organosilicon polymer prepared in Example 7 was used in the preparation of porous SiC ceramics.

[0162] The porous SiC ceramic was prepared by the following method:

[0163] To the organosilicon polymer prepared in Example 7, 60 wt% polyacrylonitrile-acrylamide foamed microspheres from Yizheng Futian Trading Co., Ltd. and 2 wt% tert-butyl peroxide were added. After thorough mixing, the mixture was placed in an oven at 120°C and kept at that temperature for 0.5 h. Then, under a nitrogen atmosphere, the temperature was increased to 1200°C at a rate of 5°C / min and held for 1 h. After natural cooling to 800°C, air was introduced and the temperature was held for 3 h. The resulting porous SiC ceramic had a density of 0.33 g / cm³. 3 The porosity is 85.1%; the chemical formula of the ceramic product is SiC. 1.06 O 0.10 .

[0164] Example 19

[0165] The organosilicon polymer prepared in Example 7 was used in the preparation of a SiC ceramic protective coating on the surface of carbon fibers.

[0166] The SiC ceramic protective coating on the carbon fiber surface is prepared by the following method:

[0167] The organosilicon polymer prepared in Example 7 was dissolved in tetrahydrofuran to prepare a 2 wt% concentration. Then, 1% (by weight of the organosilicon polymer) of benzoyl peroxide and N,N-dimethylaniline were added and mixed thoroughly. Carbon fibers treated at 500°C under a nitrogen atmosphere for 2 hours were immersed in the above solution. Afterward, they were removed, dried, and then heated to 1200°C at a rate of 2°C / min under a nitrogen atmosphere and held for 1 hour to obtain carbon fibers with a SiC protective coating on the surface (see Appendix). Figure 4 When heated to 1000℃ at a rate of 10℃ / min in a thermogravimetric analyzer, the mass retention rate was 89%; while the mass retention rate of pure carbon fiber was only 0.9%.

[0168] By comparing Comparative Example 1 with Example 1, and Comparative Example 2 with Example 2, it can be seen that compared to the monomer ClCH2SiCl 1.25 (CH3O) 1.75 or ClCH2SiCl 0.75 (CH3O) 2.25 monomer Cl3CSiCl 1.25 (CH3O) 1.75 or Cl3CSiCl 0.75 (CH3O) 2.25 The introduction of [the substance] significantly improves the synthesis yield, molecular weight, ceramic yield, and storage life of organosilicon polymers.

[0169] For the organosilicon polymer of this invention, the content of unsaturated crosslinking groups is crucial. A suitable content of crosslinking groups is beneficial for improving ceramic yield; too low a content leads to a decrease in ceramic yield; and too high a content results in a decrease in ceramic yield and an increase in residual carbon content due to the degradation of the crosslinking groups. A comparison of Comparative Examples 1 and 3 shows that a reduction in unsaturated crosslinking groups leads to a decrease in ceramic yield. However, for this invention (as compared with Examples 1, 3, and 4), due to the high molecular weight of the synthesized organosilicon polymer, although the content of crosslinking groups is reduced, it does not adversely affect the ceramic yield; on the contrary, it is beneficial for improving the ceramic yield and reducing the residual carbon content (C / Si ratio).

[0170] A comparison of Examples 2, 11, and 5 shows that when Cl3CSiCl 0.75 (CH3O) 2.25 When the content of silane monomer is increased from 10% to 40%, the reaction yield, molecular weight, and ceramic yield of the resulting liquid organosilicon polymer are compared with those without Cl3CSiCl. 0.75 (CH3O) 2.25 The monomer comparison ratio 2 was greatly improved, but when Cl3CSiCl 0.75 (CH3O) 2.25 When the monomer content is increased to 50%, the reaction yield of the resulting organosilicon polymer is significantly lower than that of polymers with monomer content of 10%–40%, and the decrease is close to that of Comparative Example 2. Therefore, Cl3CSiCl 0.75 (CH3O) 2.25 The content should not exceed 50%.

[0171] A comparison of Examples 4 and 6 shows that, during the Grignard reaction stage, the monomer Cl3CSiCl 1.25 (CH3O) 1.75 The feeding time is later than ClCH2SiCl 1.25 (CH3O)1.75 This is more conducive to increasing the molecular weight, reaction yield, and ceramic yield of organosilicon polymers.

[0172] By comparing Examples 1, 8, and 9, from Example 8 to Example 9 and back to Example 1, the monomer Cl3CSiCl 1.25 (CH3O) 1.75 The content gradually increases, with the monomer Cl2CHSiCl 1.25 (CH3O) 1.75 As the content gradually decreases, the molecular weight of the liquid organosilicon polymer gradually increases. This indicates that the monomer Cl3CSiCl 1.25 (CH3O) 1.75 The addition of [specific component] relative to the addition of monomer Cl2CHSiCl 1.25 (CH3O) 1.75 It has better effects on improving molecular weight, yield, and ceramic yield.

[0173] A comparison of Examples 8, 12, and 10 shows that when Cl2CHSiCl 1.25 (CH3O) 1.75 When the content of silane monomer is increased from 20% to 50%, the reaction yield, molecular weight, and ceramic yield of the resulting liquid organosilicon polymer are compared with those without Cl2CHSiCl. 1.25 (CH3O) 1.75 The monomer comparison ratio 1 was greatly improved, but when Cl2CHSiCl 1.25 (CH3O) 1.75 When the monomer content is increased to 60%, the reaction yield of the resulting organosilicon polymer is significantly lower than that of polymers with monomer content of 20%–50%, and the decrease is close to that of Comparative Example 1. Therefore, Cl2CHSiCl 1.25 (CH3O) 1.75 The content should not exceed 60%.

[0174] A comparison between Comparative Example 4 and Example 14 shows that for organosilicon polymers without unsaturated groups, Cl3CSiCl 1.25 (CH3O) 1.75 The introduction of [a specific ingredient] significantly increases the molecular weight of organosilicon polymers, thereby improving ceramic yield.

[0175] As can be seen from Examples 15 to 19, the organosilicon polymer synthesized using the present invention can be used to prepare SiC. f / SiC composite materials, C f SiC composite materials, porous SiC foam, and SiC coatings, etc.

[0176] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.

[0177] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.

[0178] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.

Claims

1. A method for preparing liquid organosilicon polymer, characterized in that, Includes the following steps: by , and As a single entity, or as and As a monomer, a liquid organosilicon polymer is prepared by Grignard reaction and reduction reaction steps, wherein X is selected from one or more halogen groups; R1, R2, R3, R4, R5, R6, R7, R8 and R9 are independently selected from one or more of H, halogen, alkyl, alkoxy, aryl, substituted aryl, and unsaturated groups; at least one of R1, R2 and R3 is a halogen or alkoxy group; The Grignard reaction step includes: monomer Add to an ether solvent containing magnesium metal, and after the feeding is complete, add... The reaction proceeds with unsaturated haloalkanes and / or their Grignard reagents; or, monomers... Add to an ether solvent containing magnesium metal, and after the feeding is complete, add... and The reaction proceeds with unsaturated haloalkanes and / or their Grignard reagents; Unsaturated haloalkanes are alkenes or alkynes containing CX groups, where X is a halogen element; When included , , When there are three monomers, the monomers and The sum of the molar amounts of these components accounts for 10% to 50% of the total molar amounts of the three monomers; when containing and When there are two monomers, the monomers The molar amount of the two monomers accounts for 10% to 40% of the total molar amount of the two monomers.

2. The preparation method according to claim 1, characterized in that, The Grignard reaction is carried out at 45~85℃ for 1~50h.

3. The preparation method according to claim 1, characterized in that, The reduction reaction step includes: adding a reducing agent to the product of the Grignard reaction to carry out a reduction reaction.

4. The preparation method according to claim 3, characterized in that, The reduction reaction is carried out at 45~85℃ for 1~40h.

5. The liquid organosilicon polymer prepared by the preparation method according to claim 1.

6. The application of the liquid organosilicon polymer as described in claim 5, characterized in that, The applications include one or more of the following: a. Applications in the preparation of SiC ceramic matrix composites, porous SiC ceramics, or SiC fibers. b. Preparation of protective coatings for use on carbon materials, metals, ceramics, or ceramic matrix composites. c. Applications for filling and / or reinforcing carbon materials, metals, ceramics, or ceramic matrix composites. d. Applied to the joining of ceramics or ceramic matrix composites, e. Applied to the molding of complex SiC ceramic components.

Citation Information

Patent Citations

  • Ultrasonic radiation preparation method of liquid-state polycarbosilane

    CN109400886A

  • Liquid polycarbosilane as well as preparation method and application thereof

    CN115678019A